2015
DOI: 10.1016/j.dcn.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mid-adolescent neurocognitive development of ignoring and attending emotional stimuli

Abstract: Appropriate reactions toward emotional stimuli depend on the distribution of prefrontal attentional resources. In mid-adolescence, prefrontal top-down control systems are less engaged, while subcortical bottom-up emotional systems are more engaged. We used functional magnetic resonance imaging to follow the neural development of attentional distribution, i.e. attending versus ignoring emotional stimuli, in adolescence. 144 healthy adolescents were studied longitudinally at age 14 and 16 while performing a perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 55 publications
12
48
0
Order By: Relevance
“…Therefore, a 2 × 2 × 2 ANOVA with the between‐subject factor group (ADHD, TD), and the within‐subject factors attention (attending emotional stimuli, ignoring emotional stimuli) and emotional valence (negative, positive) was analyzed. Overall, regions overlap with those found in Vetter et al () and Pilhatsch et al () using the same paradigm in TD adolescents. Results showed higher activity in the left IFG ( x , y , z = −51, 27, 12; k = 87, t = 4.86, cluster‐level p = .01) and left middle temporal gyrus ( x , y , z = −60, −57, 21; k = 103, t = 4.26, cluster‐level p = .006) for attending versus ignoring emotional stimuli.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, a 2 × 2 × 2 ANOVA with the between‐subject factor group (ADHD, TD), and the within‐subject factors attention (attending emotional stimuli, ignoring emotional stimuli) and emotional valence (negative, positive) was analyzed. Overall, regions overlap with those found in Vetter et al () and Pilhatsch et al () using the same paradigm in TD adolescents. Results showed higher activity in the left IFG ( x , y , z = −51, 27, 12; k = 87, t = 4.86, cluster‐level p = .01) and left middle temporal gyrus ( x , y , z = −60, −57, 21; k = 103, t = 4.26, cluster‐level p = .006) for attending versus ignoring emotional stimuli.…”
Section: Resultssupporting
confidence: 72%
“…As a plausibility check, RT and valid trials for the TD group were in the range as recently reported in a similar sample (Vetter et al, ).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This fair to good reliability fits to the behavioral developmental effects in all paradigms: Adolescents became faster from age 14 to 16 in both the emotional attention 16 and cognitive control paradigm. The log-transformed discount parameter increased which can probably be interpreted with decreased impulsivity from age 14 to 16 22 .…”
Section: Resultssupporting
confidence: 59%
“…The emotional task has been shown to yield valid results both on the behavioral and neural level 15, 16 . It activates the fusiform gyrus, the inferior and middle frontal gyrus, and the inferior parietal lobe.…”
Section: Introductionmentioning
confidence: 99%